Dalit Christian Activism as Affective Counter - Public - Ponniah, J. (University of jaffna, 2024)
Coined by Zizi Papacharissi (2014) , the idea of affective publics refers to the changing nature of the contemporary publics and focuses on their relational, processual, and performative character in a complex digital/mobile media environment, constituting new networks of communication. This new mode of publicness is brought about not so much by communicative rationality but by emotive resonances and affective responses that take place among citizens, and, between citizens and digital media technology, both enabling and restraining public articulations. Politics of religious nationalism in different nation states of our era produces affective publics across the globe by creating among the religious majority a sense of fear and threat towards religious/ethnic other(s), producing them as ‘minoritized’ communities’ and portraying them as ‘enemies within’. To such a situation of religious nationalism in India, this paper argues that the Christian Dalits do not remain as mute spectators. Pursuing the political struggle for social democracy and the Dalits’ right to equal citizenship inaugurated by Dr. Ambedkar, Christian Dalits of India today are engaging in a thoughtful multi-directional political activism thereby evolving an affective counter-public by enlisting the support of a range of interlocutors and stakeholders across India and beyond.
Keywords: Affective publics; Emotive resonances; Minoritized communities; Christian dalits of india; Political activism